Cister a Sul do Tejo: o Mosteiro de S. Bento de Cástris e a Congregação Autónoma de Alcobaça (1576-1776) - Conde, Maria Antónia Marques Fialho Costa (2014)
The history of São Bento de Cástris convent, the oldest Portuguesa Cistercian community south of Tagus, has always been closely connected with Alcobaça, having been affiliated at its foundation to the Abbey of Santa Maria. In 1274, having adopted the usual form of Cistercian observance, the nuns took the solemn vows of Chastity, Poverty and Obedience and a life of hermetic retreat: the convent was born. The building and site were a natural reflection of requirements, fora Cistercian establishment: it was some distance from the urban area, situated on the side of a small valley formerly planted with vineyards, with propitiously good water resources and soils. It was well-designed for the functioning of the convent: work was begun to considerably the initial gothic building in the first quarter of the 16th century, and continued over the course of the next two centuries, although much of this later work was devoted to the decorative arts. This was the richest period of the convent in terms of culture, which is clear from the Choir books, wich constitute the greatest collection of its type in Évora. Based on a case study of São Bento de Cástris convent, a female Cistercian community, this doctorate dissertation, centred on the post-Tridentine period, till the mesures of the Marquis of Pombal, will seek to: understand the relations of the convent with the local and national powers, and its reaction with the religious changes of the XVI century in. Europa (Council of Trent) and in Portugal (the formation of the Autonomous Congregation of Alcobaça); characterise the population of the convent, in different levels, attempting to identify behavioural patterns wich provide an understanding of political, socio-ecomonic and mental changes, occurring in the area throughout the Ancien Régime; study a part of this population, the cases considered as significant in the life of the community: abbesses or other members of the internai hierarchy or ordinary nuns who stood out from among their peers (good mangement vis-à-vis the bad managements of goods, literary production, etc.), forming a local elite, in relationship with the world they belong outside the limits of the convent; recognize the importance of the dotes (dowry) in this temporal context to the economical life of the monastery (the number of nuns depends on the resources of the community), and how the marriage in religion is an option to the secular marriage; identify the signs of mystical life in the cloister, so typical of barroc mentality; reconstitute the way in wich the patrimony of this convent was built up by using the resolutions of the Precepts, civil law and canon law; assess the extent to wich regulations and external forces conditioned the everyday life in religious houses, and identify the limits on the exercise of free choice by their internal organs. Therefore, the specificity of the convent in question, and the particular situation of Portugal in socio-political and religious context of Tridentine Europe (dynastic union and the weight of church, for example) will not allow for the general application of results obtained in this thesis. At the very least, it could provide an analytical framework for future work carried out on other religious houses, specially female communities, not only in Portugal, but also in. Europe, specially to compare different realities in the same historical time (XVI-XVIII centuries).